2019
DOI: 10.1016/j.jbo.2019.100238
|View full text |Cite
|
Sign up to set email alerts
|

Tumor derived EDIL3 modulates the expansion and osteoclastogenesis of myeloid derived suppressor cells in murine breast cancer model

Abstract: Epidermal growth factor-like repeats and discoidin I like domain 3 (EDIL3) is an integrin ligand which is implicated in bone metabolism and bone marrow myelopoiesis. Recently, myeloid derived suppressor cells (MDSCs) as osteoclast progenitor have been demonstrated in several kinds of cancers including breast cancer. In this paper we explored the association between tumor derived EDIL3 and MDSCs in a murine breast cancer model. Knockdown of EDIL3 in MDA-MB-231 breast cancer cells inhibited the expansion of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Furthermore, MDSCs serve as osteoclast progenitors in breast cancer and enhance cancer-associated osteolysis. MDSCs differentiate into osteoclasts through NO signaling and cancer cells, thereby promoting osteolysis during bone metastasis in breast cancer, as reported in a murine model of breast cancer [49,146,147]. In breast cancer, the SDF-1/CXCR4 and CXCL5/CXCR2 axes recruit Gr-1 + CD11b + myeloid cells, activate MMP, and upregulate TGF-β1, which contributes to metastasis in mouse models injected with a breast cancer cell line (4T1) [124].…”
Section: Nonimmune Mechanism Of Mdscs In Breast Cancer Progression Anmentioning
confidence: 74%
“…Furthermore, MDSCs serve as osteoclast progenitors in breast cancer and enhance cancer-associated osteolysis. MDSCs differentiate into osteoclasts through NO signaling and cancer cells, thereby promoting osteolysis during bone metastasis in breast cancer, as reported in a murine model of breast cancer [49,146,147]. In breast cancer, the SDF-1/CXCR4 and CXCL5/CXCR2 axes recruit Gr-1 + CD11b + myeloid cells, activate MMP, and upregulate TGF-β1, which contributes to metastasis in mouse models injected with a breast cancer cell line (4T1) [124].…”
Section: Nonimmune Mechanism Of Mdscs In Breast Cancer Progression Anmentioning
confidence: 74%
“…Study showed that EDIL3 promoted tumors angiogenesis in vivo [14]. To determine whether EDIL3 also modulated dermal vascular network expansion in psoriatic mouse models, we conducted immuno uorescence analysis in skin sections and double immuno uorescence staining with DAPI and CD31 was evaluated via two-photon confocal laser microscopy.…”
Section: Edil3 Promoted Angiogenesis In Vivomentioning
confidence: 99%
“…The RGD motif can bind with integrin, then effect ECs functions including survival, adhesion, migration and angiogenesis [8,11,12]. During angiogenesis in early embryogenesis [13], tumor [14] and ischemic tissue [15], EDIL3 is an important molecular for mediating ECs functions. In present, whether EDIL3 derived from DMSCs can impact on ECs in psoriasis is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…When the steady state is not reached, a heterogeneous population of immature myeloid lineage cells, MDSCs, are produced [184]. Therefore, MDSCs are present in low concentration in healthy individuals, but as a result of chronic inflammation mediated by cytokines and chemokines produced by malignant cells, MDSCs are exponentially produced and accumulate in the tumor [185,186].…”
Section: Myeloid-derived Suppressor Cell Membrane-coated Npsmentioning
confidence: 99%